Divorce in Balinese Customary Law and the Social Dynamics of Women - Darmayanti, Resty Rahayu; Syamsu A Kamaruddin; Arlin Adam; Ahmadin (Muhammadiyah University of Makassar, 2026)
Divorce in the Balinese indigenous people is not only understood as the end of a conjugal relationship, but also as part of the social dynamics governed by customary law and the patrilineal kinship system. This research aims to understand divorce as a social process within the framework of Balinese customary law and examine the social dynamics experienced by women after divorce. The research uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observations, and documentation of women who have experienced divorce, and supported by information from families, communities, and traditional leaders. The results of the study show that the practice of divorce in Balinese customary law is not entirely in the personal realm, but involves social control through the family and customary institutions. Women tend to experience changes in social position, social pressure, labeling, and changes in social relations in the family, society, and with children after divorce. The social relations that are formed are not entirely equal, because women are in a more vulnerable position in the social structure. These findings show that customary law not only serves as a mechanism for conflict resolution, but also serves as a space for the reproduction of gender inequality in society. Keywords: Divorce; Balinese Customary Law; Women's Social Relations; Gender Inequality